Conceptual (methodological) basis for the development of the Strategy of socio-economic development of the city - F. K. Mirhadzhaev (Путеводитель предпринимателя, 2020)
This article discusses issues related to the organization of the system of strategic planning at the municipal level, the preparation of the Strategy of socio-economic development.